The Magdalenian colonization of southern Germany. - Jochim, Michael (American Antropological Association, 1999)
Although the topics of migration and colonization have received renewed archaeological attention in recent years, their relevance to the deep past of hunter-gatherer archaeology has been debated. The Magdalenian colonization of southern Germany after the last glacial maximum, ca. 15,000-13,000 B.P., presents a case study in which many of the debated issues can be explored. Environmental change and relative demographic pressure played a causal role in population movements, leading to a gradual, discontinuous expansion from the Franco-cantabrian refugium. Active social strategies to overcome the risks facing frontier groups helped maintain remarkable uniformity in material culture across hundreds of kilometers, despite shifts in subsistence and settlement patterns required in the newly occupied areas.